OPTIMALISASI ELEKTRONIK MODUL MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM DENGAN PLATFORM 3D PAGEFLIP DI MAN 1 SITUBONDO - Hasanah, Lina Fajariyah; Yunus, Mochammad; Ni'mah, Mamluatun; Fatimah, Nur (ANDRAGOGI, 2023)
The increasingly rapid technology makes people have to innovate, demanding that everything must be instant and feel reached through technology, including in the world of education. An interesting presentation in the world of education is demanded to always present interesting things. One of the highlights today is the presentation of teaching for students, one of which is teaching modules for students. Printable modules that are more sophisticated help teachers and students make it easier in all aspects of the lesson, one of which is Islamic cultural history (skiing) lessons. It is known that the purpose of skiing lessons is a complicated lesson from the aspect of memorizing, setting dates and the complexity of historical events, so with the presence of electronic modules using the 3d pageflip platform it makes everything easier in learning will be more fun and the electronic aspects of the module in the platform 3d pageflip considers several components to make it easier for a teacher to make: (1) content feasibility, (2) language that is easy to understand (3) systematic historical events in maple ski (4) graphs that can be understood. This research method uses the SPSS application by giving a validity value against more valid 3D pageflip application.